On the thermal conductivity of adhesively bonded and sintered Hollow Sphere Structures (HSS) - Fiedler, Thomas (Transtech Publications, 2007)

(untitled)
This paper is on the geometrical effective thermal conductivity of hollow metal sphere structures. Two different technologies of joining, namely adhesive bonding and sintering, are considered. The spheres are arranged in the nodes of a cubic primitive lattice and connected by an adhesive layer, respectively directly joined by sintering. Furthermore, the influence of the cell wall thickness of the spheres on the thermal conductivity is investigated.